Síntese e caracterização de membranas de acetato de celulose, obtido do bagaço de cana-de-açúcar, e blendas de acetato de celulose com poliestireno de copos plásticos descartados - Meireles, Carla da Silva (2007)
In the present dissertation, the synthesis and characterization of cellulose acetate membranes as well as cellulose acetate and polystyrene blends, were studied. Recycled materials were used to produce the blends. Cellulose acetate (CA) was produced from sugarcane bagasse, and waste plastic cups were used as polystyrene (PS) source. Blends, produced with different CA/PS ratios, were characterized regarding the miscibility of their components. The techniques utilized for membrane characterization were Fourier Transform Infrared Spectrometry (FTIR), Differential Scanning Calorimetry (DSC), Thermogravimetric Analysis (TGA), Scanning Electron Microscopy (SEM) and measurements of water diffusion through the membranes. The results confirmed the existence of miscibility microregions in the blends and indicated a region of transition when 30% PS was used, indicating a limit for a possible phase inversion between the matrix and the disperse phase. The membranes were also characterized regarding their properties of water flux, PEG rejection (utilizing an aqueous solution 1% w/v of polyethylene glycol, PEG, 45 kDa and 80 kDa) and ion diffusion by dialysis. The experiment of ion diffusion by dialysis showed that the coefficients of ion diffusion of both the pure CA and the CA/PS blends were comparable to previously reported values for commercial cellulose triacetate membrane. These results showed that the membrane produced from recycled materials, sugarcane bagasse and polystyrene cups, behaves likewise the commercial material. Regarding permeation driven by difference of pressure, 12% w/w membrane showed the best performance and rejected 27% PEG 80 kDa. These preliminary results showed that this membrane should be better evaluated in the range of application comprehending ultrafiltration or microfiltration processes.